Advancements in mental skills training (Routledge, 2021)
The book comprehensively examines the use of mental skills training for athletic performance and well-being from a cross-cultural perspective. It begins by introducing theoretical advancements related to mental toughness, cultural factors, performance optimisation and mindfulness. It goes on to examine the technological advancements related to mental skills training, outlining how mobile technologies can be used to measure and train perceptual-cognitive skills, and the effectiveness of virtual reality in mental training. The book concludes by discussing emerging topics, such as how sports psychology can incorporate spirituality, minority groups in sport and the impact of prejudice, and referee career development.